Performance and techno-economic analysis of humid air turbines for commercial marine applications - Brighenti, Giovanni D. (Cranfield University, 2018)
The curb in SOᵪ and NOᵪ emissions, led by legislation both globally and in emission controlled areas, could eventually result in a ban of heavy fuel oil (HFO) for commercial marine applications. This could end in a window opening for advanced gas turbine-based power plants in the market of deep sea propulsion, currently dominated by slow-speed two-stroke diesel engines. Previous studies have identified humid air turbine (HAT) as promising gas turbine- based cycles, able to compete with diesel engines in terms of maximum thermal efficiency. However, no emphasis has yet been given to the identification of the potential of the reheated HAT cycle. This cycle features notably better performance relatively to a single burner system, and may promote the exploitation of humid cycle power plants in applications where high thermal efficiency and high power-to-plant size rations are of importance. This thesis presents an analysis of the impact of the technology level of the main component on the performance of the HAT cycle. Part-load performance analyses of the humid air cycle as a whole system is performed. Moreover, a techno-economical study of a commercial vessel powered by a HAT cycle for a given commercial route is used to directly compare the annual cost of machinery of the cycle with a diesel engine. The research outcomes confirm the higher thermal efficiency of the reheated HAT cycle and show the impact of technology level of the heat exchangers on the performance of the cycle. The part-load analyses of the HAT cycle show low penalties in performing away from the design condition. The comparison between the HAT and diesel engine, and advanced diesel engines, demonstrate the potential of the HAT cycle as prime mover of commercial marine vessels. Overall this research is a step forward towards the understanding of the feasibility of humid air turbines for replacing diesel engines in commercial marine applications or for applications where the density of power is of competitive advantage.
PhD in Aerospace